Competitive and non-competitive zinc, copper and lead biosorption from aqueous solutions onto flax fibers. (December 2020) - Kajeiou, Meriem; Alem, Abdellah; Mezghich, Soumaya; Ahfir, Nasre-Dine; Mignot, Mélanie; Devouge-Boyer, Christine; Pantet, Anne
Abstract: Competitive and non-competitive batch experiments were conducted on flax fibers to study Zn 2+, Cu 2+, and Pb 2+ ions biosorption performance. Biosorption efficiency was dependent on contact time, pH, and biosorbent concentration. The results under competitive conditions were different from those obtained in non-competitive form. A high affinity of lead, with a selectivity sequence in general of Pb > Cu > Zn was observed. The biosorption data fitted very well the Langmuir model for lead in both types of solutions and for zinc and copper in the monometal form. The fit with the Freundlich model was not as successful, except for copper in the ternary system. Regarding zinc under competitive conditions, the sorption process was quite difficult and thus the equilibrium data could not fit well the adsorption models. The maximum adsorption capacities (mmol.kg −1 ) were respectively 112, 122 and 71, for Pb, Cu and Zn in the single metal ion solution and 82, 57 and 8 only in the ternary, showing thus a high competition between metal ions when added simultaneously. Overall, lead could still be efficiently removed in spite of the presence of other ions while zinc would be overcome in the presence of lead and copper. Graphical abstract: Image 1 Highlights: Flax fibers were used to remove zinc, copper and lead ions from aqueous solutions. The selectivity sequence was Pb > Cu > Zn in both single and multimetal systems. Higher adsorption was observed in the single system for the three heavy metals. Lead is the less affected ion by competition. Zinc was overcome in the presence of lead and copper.